Preventing Abuse of Trademark Registration Through Speculative Filings in Indonesia - Brian Valentino Lates Cal Cariver; Mieke Yustia Ayu Ratna Sari (Jurnal Ilmiah Kebijakan Hukum, 2026)
The practice of blocking and speculative trademark applications exploits administrative gaps in the first-to-file system to secure advantages without genuine commercial intent. This article employs statutory, conceptual, case-law, and comparative doctrinal approaches. Drawing on the jurisprudence of the Court of Justice of the European Union, this article shows that bad faith is primarily assessed through intention to use. However, the Indonesian normative framework has not operationalized the notion of “unfair business competition” into objective and verifiable standards, as it lacks measurable indicators to assess the applicant’s intent at filing. Consequently, examination remains largely formalistic and reactive, rendering the system vulnerable to speculative applications. This article conceptualizes blocking and speculative applications as manifestations of bad faith and recommends proportionate administrative reforms, including the introduction of an intention-to-use declaration, the development of a red-flag checklist based on operational indicators such as chains of applications, offers to sell, and absence of genuine use, as well as cross-border database verification for early detection. These measures aim to strengthen preventive mechanisms at the registration stage without undermining the first-to-file principle.